Processos de separação de materiais valiosos de telas lcd de telefone celular - Fuchs, Miria da Silva (2013)
The proposal of this work is separate the liquid crystal display (LCD) screen of cell phones in disuse, removing polymers which are adhered to the glass screen by using an appropriate solvent, and then perform the glass comminution to leaching the metal oxides that form part of the composition of the LCD screens of cell phones, as well as the screens of televisions, computers, digital clocks and other devices that have liquid crystal displays. With these proceedings, the polymeres, glass and metallic oxides are separated and can be recovered and reused, avoiding the consumption of non-renewable raw materials. Several tests are made under different conditions of temperature, time, ratio solute/solvent, particle size comminution and acid concentration in the leaching. The amount of indium and tin present in LCD screens, in the form of indium tin oxide (ITO) is analyzed in an apparatus for atomic absorption flame, which provides the same amount of the leaching solution. Compared with the amount of indium extracted in a solution of aqua regia 1:20, considered the condition of maximum extraction metal oxides, the quantity of indium recovered, in 1M sulfuric acid solution in 1:10 at 90ºC for 2 hours with those procedures was 98,74%.